A Vicious Circle of Clonal Haematopoiesis of Indeterminate Potential and Cardiovascular Disease - Ehlert, Carolin A.; Hilgendorf, Ingo (Hämostaseologie, 2021)
Clonal haematopoiesis of indeterminate potential (CHIP) represents a recently identified overlap between cancer and cardiovascular disease (CVD). CHIP develops as a result of certain acquired somatic mutations that predispose to leukaemia, but clinically even more prevalent, associate with increased risk for CVD and CVD-related death. Experimental studies suggest a causal role for CHIP aggravating inflammatory processes in CVD, and recent epidemiologic and genetic studies indicate that classical CVD risk factors may increase the risk of acquiring CHIP driver mutations, thus fuelling a vicious circle. The potential mechanism underlying the associative link between CHIP and CVD and mortality has been the focus of a few recent excellent experimental and observational studies which are summarized and discussed in this concise non-systematic review article. These data support a pathomechanistic view of a spiralling vicious circle in which CHIP aggravates the inflammatory immune response in CVD, and CVD-driven elevated haematopoietic activity promotes CHIP development.
Keywords: clonal haematopoiesis; cardiovascular disease; somatic mutation